In Vitro Efficacy of Gingerol-Containing Emprit Ginger (Zingiber officinale var. amarum) Extract Against Fusarium oxysporum - Maharani, Jane Tiara; Jayanti, Ruth Meike; Hutagalung, Sarawinda; Herawati, Maria Marina (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the antifungal activity of emprit ginger (Zingiber officinale var. amarum) extract containing 6-gingerol against Fusarium oxysporum under in vitro conditions and to determine the concentration with the highest inhibitory effect. The experiment was conducted using a completely randomized design with six treatments consisting of a negative control, emprit ginger extract at concentrations of 0.5%, 1.5%, 2.5%, and 5%, and a synthetic fungicide as the positive control, with five replications for each treatment. The 6-gingerol content was quantified using High-Performance Liquid Chromatography (HPLC), while antifungal activity was assessed using the poisoned food technique on Potato Dextrose Agar (PDA) medium. Data were analyzed using analysis of variance (ANOVA), followed by the Honestly Significant Difference (HSD) test at a 5% significance level. The results revealed that emprit ginger extract contained 6-gingerol at 8.082 µg/mL. Growth inhibition of F. oxysporum increased with increasing extract concentrations, reaching the highest inhibition (56.49%) at 5% extract concentration. Under the tested in vitro conditions, this treatment showed higher inhibition than the positive control (43.26%). The extract also induced morphological alterations, including reduced mycelial density, pigmentation changes, and restricted colony expansion. These findings indicate that emprit ginger extract containing 6-gingerol has potential as a botanical biofungicide candidate for suppressing F. oxysporum. Further validation through in vivo and field-scale studies is required before practical application.